Асимптотическое поведение произведений случайных матриц со значениями в разрешимой алгебре Ли - Чани, А.С. (Український математичний журнал, 1993)
The index of exponential growth is found for the products of random matrices with values on a solvable Lie algebra. The result is expressed via the eigenvalues of the terms.